Intravital characterization of tumor cell migration in pancreatic cancer. Issue 3 (1st September 2016) - Beerling, Evelyne; Oosterom, Ilse; Voest, Emile; Lolkema, Martijn; van Rheenen, Jacco
ABSTRACT: Curing pancreatic cancer is difficult as metastases often determine the poor clinical outcome. To gain more insight into the metastatic behavior of pancreatic cancer cells, we characterized migratory cells in primary pancreatic tumors using intravital microscopy. We visualized the migratory behavior of primary tumor cells of a genetically engineered pancreatic cancer mouse model and found that pancreatic tumor cells migrate with a mesenchymal morphology as single individual cells or collectively as a stream of non-cohesive single motile cells. These findings may improve our ability to conceive treatments that block metastatic behavior.